IMPLEMENTASI MEDIA KANTONG PERKALIAN DAN METODE JARIMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN NGIJO 01 PADA MATERI PERKALIAN BILANGAN CACAH - Endang Tri Kartika Larasati; Trimurtini; Ika Ratnaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The difficulty of third-grade elementary school students in understanding the arithmetic operations of whole numbers remains a challenge in mathematics learning. Low learning outcomes and conventional learning approaches characterize this. The purpose of this study was to determine the effect of using multiplication bag media and the jarimatic method in improving elementary school students' learning outcomes. This study was conducted in the odd semester of the 2025/2026 academic year with a quantitative approach using a quasi-experimental design, with the type of design used being a nonequivalent control group. The research subjects consisted of two classes, namely the experimental class that received treatment in the form of the application of multiplication bag media and jarimatic method, and the control class that used picture media and memorization methods. Data were collected through tests, observations, and documentation. Data analysis used normality tests and homogeneity tests as prerequisite tests, as well as paired sample t-tests and independent sample t-tests for hypothesis testing. The results showed that the significance value in the independent sample t-test was <0.001, which indicated a difference in mathematics learning outcomes between the experimental and control classes. Furthermore, a paired sample t-test showed significant improvements in both classes, with the experimental class's average pretest score of 53.80 increasing to 60.95 on the posttest, while the control class also experienced an increase from a pretest average of 58.16 to 75.86 on the posttest. These findings demonstrate that the integration of multiplication bags and the Jarimatic method is effective